PERAN PERMAINAN BERBASIS DIGITAL DITINJAU DARI MINAT BELAJAR DAN LITERASI PADA SISWA KELAS V DI SD MUHAMMADIYAH 4 SURABAYA - Nabila Sekardini, Putri; Ichda Wahyuni, Holy; Naila, Ishmatun (Nirta Learning Centre, 2026)
The development of digital technology encourages innovation in the learning process in elementary schools, particularly in efforts to foster learning interest and strengthen students' literacy skills. This study aims to describe the role of digital-based games as a learning medium in supporting learning interest and literacy skills in elementary school students. Observation, interviews, and documentation are the data collection techniques used in this study. The research subjects consisted of students and teachers at the elementary school level who implemented educational games in learning activities. The results showed that digital-based games demonstrated student engagement through learning activities that were more interesting, interactive, and in accordance with the characteristics of the digital generation. In addition, activities in digital games contributed to strengthening literacy skills, particularly through understanding instructions, reading texts, and completing story-based tasks. This study confirms that digital games can be an effective learning medium when used in a targeted manner and in accordance with learning objectives. This research is expected to serve as a reference for teachers and schools in developing innovative and contextual learning strategies.